Cross spectral densities in random vibration analysis. (5th August 2014) - Robson, J.D.
The paper aims to consider the particular character of multi–variate random processes as relevant in random–vibration problems. The ideas of cross spectral density and coherence are introduced and the relevance of matrix formulation is emphasized. The limited nature of analogy with the problem of harmonic response is also emphasized, but the value of the analogy is demonstrated. The consequences of complete coherency are discussed, some aspects of response formulation in terms of normal co–ordinates are explored and the concept of partial coherency is explained.